The effect of fiscal policy on personal and regional distribution of income : Argentina 1995-2010 - Cont, Walter Alberto (2015)
This paper studies the effect of consolidate –national and provincial– fiscal policy in Argentina on income distribution, building a novel panel data for 1995‐2010 considering the 24 jurisdictions and quintile groups within provinces. We allocate expenditures, taxes and transfers among provinces and among people within provinces, according to benefit and incidence principles, avoiding double accounting, and build three measures of income: ex ante, interim, and ex post (or extended) income. We find that i) personal income inequality increased between 1995 and 2002, and then reverted the trend; ii) the trends in income inequality have a parallel with the different macroeconomic regimes nested in the sample (convertibility between 1995 and 2001 and post convertibility since 2002); iii) the effect of fiscal policy is a reduction in the Gini of 6 points in 1995, 5 points in 2002 and 10 points in 2010; iv) the mix of instruments to redistribute income changed with time towards cash transfers and against in‐kind expenditures; iv) provincial budgets contribute strongly to progressivity; v) social expenditure is the most important redistribution tool, but economic services have grown in size between sub‐periods, pushed by government subsidies in energy and transport; vi) Intermediate and Lagged Groups benefit more from redistribution, the latter benefiting strongly from in‐kind expenditures; vii) the effect of fiscal policy on regional and personal distribution of income is complementary, the former representing 41% of the latter (although decreasing in the second part of the sample); and vi) the paper measures the distribution of budget but leave aside the distribution of results (e.g., expenditure performance).